Cumulative stressful events and mental health in young adults after 10 years of Wenchuan earthquake: the role of social support - Xiao-Yan Chen; Dongfang Wang; Xianchen Liu; Xuliang Shi; Andrew Scherffius; Fang Fan (European Journal of Psychotraumatology, 2023)
Background: After a natural disaster, stressful events often continue to accumulate, affecting individuals in a different manner than the original disaster never occurred. However, few studies have examined these associations, the cumulative impacts of stressful events on mental health outcomes, and the role of social support. This study examined the prospective association between cumulative stressful events and mental health problems and the role of social support in young adults. Methods: 695 participants provided available data on earthquake exposure, childhood maltreatment, other negative life events, and social support at baseline. Depressive symptoms and posttraumatic stress disorder were assessed at baseline and 10 years after the earthquake (T10y). A cumulative stressful events index was used to evaluate the levels of cumulative stressful events. Linear regressions were used to explore the predictive effects. Results: Of 695 participants, 41.3%, 28.5%, and 7.9% reported one, two, and three stressful events, respectively. The associations between cumulative stressful events and mental health problems at T10y presented a dose–response pattern: those who experienced three events had the highest risk of mental health problems, followed by those who experienced two events and those who reported one event. Additionally, higher social support partially reduced the negative impact of cumulative stressful events on mental health. Conclusions: Cumulative stressful events are associated with mental health problems 10 years later in young earthquake survivors. Social support could reduce the negative impact, but its protective role disappears when stressful events accumulate at the highest level. These findings highlight the importance of assessing the cumulative impacts of stressful events and social support available to young disaster survivors and intervening to prevent worse mental health outcomes.